Avaliação dos fatores de risco relacionados à severidade da covid-19 em pacientes com diabetes tipo 2 de um hospital universitário da região norte entre 2020 e 2021 - LEITÃO, Loyane Tamyres Costa (2023)
Introduction: During the COVID-19 pandemic, it was observed that individuals with previous comorbidities such as cardiovascular, pulmonary and metabolic diseases, such as Type 2 Diabetes Mellitus (DM2), were at greater risk of complications when infected with the new coronavirus. Many of these patients evolved with pneumonia and worsened with Acute Respiratory Distress Syndrome (ARDS), quickly corroborating to multiple organ failure. Objective: To assess risk factors related to the severity of COVID-19 in patients with DM2. Method: Retrospective observational study of an analytical nature, developed from an interview with patients diagnosed with DM2 and COVID-19, and analysis of previous clinical and laboratory data referring to outpatient consultations at the Endocrinology and Metabology Service of a Reference Hospital in the Region North. The hypotheses were tested according to the nature of the variables, considering an alpha of 5%. Results: We studied 101 patients with DM2, all dyslipidemic, who had asymptomatic or mild (n=62), moderate (n=32), and severe (n=7) COVID-19, classified according to clinical and/or laboratory tests, according to the Ministry of Health. Of these, 35 were brown, 33 black and 33 white, with racial proportions not different depending on the clinical form (p=0.7389). As for age, the patients had an average of 59.8 ± 9.2 years, which was also not different between the clinical forms of COVID-19 (p=0.5786). Similarly, no significant differences (p>0.05) were found between the forms of COVID-19 when they were compared regarding the presence of obesity, duration of DM and dyslipidemia, glycated hemoglobin, presence and duration of SAH, total cholesterol, rate of glomerular filtration (GFR), creatinine levels and presence of peripheral arterial disease. Considering the outcome of death or cure, it was observed that the former were on average 10.8 years older (p=0.0051), had a longer time since the diagnosis of DM2 (17.2 vs. 9.1 years; p=0.0020), higher mean total cholesterol (210.0 vs. 181.8 mg/dL; p=0.0373), higher mean creatinine concentration (1.2 vs. 0.9 mg/dL; p=0.0300) and were more frequent among those with GFR<60 mL/min/1.73m² (p=0.0041), with no other associations in relation to the clinical profile. Conclusion: Risk factors such as chronic nephropathy, age, disease duration and high cholesterol were related to worse outcomes in diabetic patients who had COVID-19.